2016
DOI: 10.1161/circheartfailure.115.002756
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Function in Peripartum Cardiomyopathy at Presentation Is Associated With Subsequent Left Ventricular Recovery and Clinical Outcomes

Abstract: P eripartum cardiomyopathy (PPCM) is a pregnancy-associated cardiomyopathy of unknown cause resulting in considerable morbidity and mortality in young, otherwise healthy women. The natural history of PPCM seems to be variable although the rarity of this disease and the inconsistent diagnostic criteria that have been used in previous case series and research studies make it difficult to accurately describe the range of disease progression. Retrospective studies of patients with PPCM in the United States have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 31 publications
(27 reference statements)
4
43
0
1
Order By: Relevance
“…Two studies have addressed the question of RV function in women with PPCM at presentation, one reporting tricuspid annular plane systolic excursion ≤14 mm in 54.6% of patients 34 and another describing the association of RV function with subsequent LV recovery at 1 year. 35 In our study, we found lower RV systolic velocities on TDI and longitudinal strain in patients with post-PPCM compared with controls, suggesting some subtle residual changes of the RV. Altered TDI and 2DS indices suggest residual myocardial injury in recovered post-PPCM patients with the so-called complete LV function recovery.…”
Section: Residual LV Function Impairment In Post-ppcm Women With Lv Rsupporting
confidence: 50%
“…Two studies have addressed the question of RV function in women with PPCM at presentation, one reporting tricuspid annular plane systolic excursion ≤14 mm in 54.6% of patients 34 and another describing the association of RV function with subsequent LV recovery at 1 year. 35 In our study, we found lower RV systolic velocities on TDI and longitudinal strain in patients with post-PPCM compared with controls, suggesting some subtle residual changes of the RV. Altered TDI and 2DS indices suggest residual myocardial injury in recovered post-PPCM patients with the so-called complete LV function recovery.…”
Section: Residual LV Function Impairment In Post-ppcm Women With Lv Rsupporting
confidence: 50%
“…Right ventricular function at baseline has recently been shown to predict LV remodeling at follow up in peri-partum cardiomyopathy patients. 31 This remains unexplored in DCM.…”
Section: Predictors Of LV Remodelingmentioning
confidence: 99%
“…Only 3 prior studies have assessed the RV systolic function in PPCM outcomes. All were limited to 6 or 12 months' follow‐up . The IPAC (Investigations of Pregnancy Associated Cardiomyopathy) study, the largest of these multicenter studies, evaluated multiple quantitative echocardiographic indexes of baseline RV and LV size and function in association with LV recovery and clinical outcome at 1 year .…”
Section: Discussionmentioning
confidence: 99%
“…PPCM accounts for 5% of all women who undergo cardiac transplantation and 8% who undergo mechanical circulatory support device implantation in the United States . Despite the potential for late adverse outcomes, prior PPCM studies have largely focused on in‐hospital outcomes or those within the first year of diagnosis . Severe LV systolic dysfunction and LV dilatation have long been identified as major physiologic risk factors for adverse outcomes in PPCM .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation